Donepezil decreases annual rate of hippocampal atrophy in suspected prodromal Alzheimer's disease. Issue 9 (14th January 2015) - Dubois, Bruno; Chupin, Marie; Hampel, Harald; Lista, Simone; Cavedo, Enrica; Croisile, Bernard; Louis Tisserand, Guy; Touchon, Jacques; Bonafe, Alain; Ousset, Pierre Jean; Ait Ameur, Amir; Rouaud, Olivier; et al.
Abstract : Introduction: The purpose of this study was to study the effect of donepezil on the rate of hippocampal atrophy in prodromal Alzheimer's disease (AD). Methods: A double‐blind, randomized, placebo‐controlled parallel group design using donepezil (10 mg/day) in subjects with suspected prodromal AD. Subjects underwent two brain magnetic resonance imaging scans (baseline and final visit). The primary efficacy outcome was the annualized percentage change (APC) of total hippocampal volume (left + right) measured by an automated segmentation method. Results: Two‐hundred and sixteen only subjects were randomized across 28 French expert clinical sites. In the per protocol population (placebo = 92 and donepezil = 82), the donepezil group exhibited a significant reduced rate of hippocampal atrophy (APC = −1.89%) compared with the placebo group (APC = −3.47%), P  < .001. There was no significant difference in neuropsychological performance between treatment groups. Discussion: A 45% reduction of rate of hippocampal atrophy was observed in prodromal AD following 1 year of treatment with donepezil compared with placebo.